High-risk group and functional subtypes of non-suicidal self-injury in young adults with mental disorders - Yan, Huiru; Zhang, Yuyanan; Lu, Zhe; Li, Mingzhu; Ge, Yuqi; Mei, Dongli; Kang, Zhewei; Sun, Yaoyao; Li, Qianqian; Yan, Hao; Yang, Lei; Song, Peihua; et al. (Frontiers in Psychiatry, 2023)
Background Identifying high-risk groups of non-suicidal self-injury (NSSI) with multiple risk factors and different functional subtypes contribute to implementing person-centered interventions. Methods We investigated NSSI profiles among a sample of 258 psychiatric inpatients aged 18–25 years. All participants completed well-validated measures of internal personal and external environmental characteristics. One-hundred and ninety patients reported a lifetime history of NSSI and completed an additional NSSI assessment. A k-means cluster analysis was conducted to extract characteristics of risk factors and functional subtypes. Independent sample t-test, analysis of variance and χ2 test were used to test the difference of demographic statistical factors, risk factors and functional scores among groups with different frequency of NSSI. Results The clustering of risk factors analyses supported 4-clusters. The proportion of repeat NSSI patients was the highest (67.1%) in the group with unfavorable personal and unfavorable environmental characteristics. Functional subtype clustering analyses supported 5-clusters. Among patients with repeated NSSI, those with depression were mainly accompanied by the “Sensation Seeking” subtype (39.7%), bipolar disorder mainly supported the “Anti-suicide” subtype (37.9%), and eating disorders were mostly “Social Influence” subtype (33.3%). There was an interaction between functional subtypes and mental disorders. Limitations All participants were in treatment in a psychiatric service and the results may not be generalizable to a community sample. The data included retrospective self-report which may be inaccurate due to recall bias. Conclusion It is necessary to identify high-risk groups of NSSI who with unfavorable personal and environmental characteristics and clinical interventions need to consider the heterogeneity of patients’ functional subtypes of NSSI.